2019
DOI: 10.1017/wet.2019.60
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of foliar spray retention on creeping bentgrass

Abstract: Experiments were conducted to evaluate the impact of spray volume, nozzle type, adjuvants, the presence of dew, and their interactions on foliar retention of creeping bentgrass. Tartrazine, a common food dye, was used as a tracer in this study. Increasing spray volume from 95 L ha−1 to 1,500 L ha−1 decreased foliar retention efficiency from 98% to approximately 85%. Compared with flat-fan nozzles, air-induction nozzles delivered similar retention efficiency at all spray volumes evaluated. However, flat-fan noz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…29 Some reports demonstrated that only 15% of the pesticides sprayed on grape leaves could be retained. 30 Spraying fine, coarse, and medium droplets of c-14-glyphosate on maize leaves resulted in 51%, 65%, and 70% dropout, respectively. 31 Accordingly, enhancing the adhesion of NMs on the leaf surface would improve their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Some reports demonstrated that only 15% of the pesticides sprayed on grape leaves could be retained. 30 Spraying fine, coarse, and medium droplets of c-14-glyphosate on maize leaves resulted in 51%, 65%, and 70% dropout, respectively. 31 Accordingly, enhancing the adhesion of NMs on the leaf surface would improve their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some problems with foliar application that limit its development, for example, falling on the leaves . Some reports demonstrated that only 15% of the pesticides sprayed on grape leaves could be retained . Spraying fine, coarse, and medium droplets of c-14-glyphosate on maize leaves resulted in 51%, 65%, and 70% dropout, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Foliar spraying technology is the most common method of pest control, but its efficiency is low due to losses caused by spray drift [7][8][9]. For trees with a large crown and dense foliage, spraying is challenging [10].…”
Section: Introductionmentioning
confidence: 99%